Membangun Kebersihan 'Cleaning Day' sebagai Pilar Perubahan di Kelurahan Takkalasi dalam Mewujudkan Lingkungan yang Lebih Bersih, Sehat dan Ramah: Indonesia - Fajar Arwadi; Sahlan Sidjara; Nurul Jihad Muhammad; Nursyati; Fitria Nurul Mutmainnah (Jurusan Matematika FMIPA UNM, 2023)
This service program is a responsibility to maintain the cleanliness of the environment of an area through cleaning day activities in the Takkalasi exodus of Barru district, this activity was followed and carried out by participants of Thematic KKN Makassar State University faculties of mathematics and natural sciences supported by the local community. This environmental cleaning effort wants to build public awareness of the need for environmental cleanliness, especially where they live. This service will be carried out from July to August 2023 at Takkalasi Village, Balusu District, Barru Regency. The result obtained from this activity is that the environment around the Takkalasi sub-district area becomes cleaner, healthier and more friendly. The target of this activity starts from around the post area then the area of mosques and around community houses. This activity aims to make the public aware of the importance of environmental hygiene.